2019
DOI: 10.3892/or.2019.7229
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic agent pimozide promotes reversible proliferative suppression by inducing cellular quiescence in liver cancer

Abstract: The antipsychotic drug pimozide has been found to exhibit anticancer effects. Previously, it was demonstrated that pimozide inhibits hepatocellular carcinoma (HCC) cell growth, but its pharmacodynamic characteristics remain unclear. The aim of the present study was to investigate the reversibility and mechanism of the ability of pimozide to inhibit cell proliferation in liver cancer. Cell viability was determined by Cell Counting Kit-8 and colony formation assay. The cell cycle distribution was analyzed by flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…If intracellular ROS is responsible for the decreased proliferation, cell viability would be increased in the presence of NAC. As previously reported, treatment with 100 μM NAC increased the proliferation of RF-EMF-unexposed Huh7 cells and ASCs by 9% and 12%, respectively due to its anti-oxidation effect 33,34 . Interestingly, when both Huh7 cells and ASCs were pre-treated with NAC, cell number was increased by 49% in Huh7 and 42% in ASCs following the exposure to 1.7 GHz RF-EMF/LTE for 72 h at 2 SAR, compared with the cells only exposed to RF-EMF without NAC (Fig.…”
Section: Continuous Exposure To 17 Ghz Lte Rf-emf Delayed Cell Cyclesupporting
confidence: 80%
“…If intracellular ROS is responsible for the decreased proliferation, cell viability would be increased in the presence of NAC. As previously reported, treatment with 100 μM NAC increased the proliferation of RF-EMF-unexposed Huh7 cells and ASCs by 9% and 12%, respectively due to its anti-oxidation effect 33,34 . Interestingly, when both Huh7 cells and ASCs were pre-treated with NAC, cell number was increased by 49% in Huh7 and 42% in ASCs following the exposure to 1.7 GHz RF-EMF/LTE for 72 h at 2 SAR, compared with the cells only exposed to RF-EMF without NAC (Fig.…”
Section: Continuous Exposure To 17 Ghz Lte Rf-emf Delayed Cell Cyclesupporting
confidence: 80%
“…Recently, it has been demonstrated that PMZ inhibits P-gp, increasing apoptosis, as well as the expression of pRB and phosphorylated H2AX in KBV20 cells (425). Finally, Chen et al (426) reported that PMZ induces a reversible inhibition of proliferation in liver cancer and has an additive activity with sorafenib, which indicates the potential of pimozide as an adjuvant anticancer therapy.…”
Section: Pimozide (Pmz)mentioning
confidence: 98%
“…For example, pimozide induced ROS generation by downregulating the expression of the antioxidant enzyme catalase to suppress osteosarcoma and prostate cancer [ 166 , 167 ]. Moreover, recently, the ability of ROS generation to suppress hepatocellular carcinoma cells has been reported [ 168 ]. However, to date, pimozide has not been investigated in clinical trials to clarify the antitumor activity.…”
Section: Repurposed Drug-regulated Ros Homeostasis As a Novel Cancer Therapeutics In Oncologymentioning
confidence: 99%